Parvovirus B19-induced angiogenesis in fulminant myocarditis - Ackermann, Maximilian; Wagner, Willi Linus; Rellecke, Philipp; Akhyari, Payam; Boeken, Udo; Reinecke, Petra (European heart journal, 2020)
A 33-year-old male patient was admitted to our hospital with fever, diarrhoea, and symptoms of cardiogenic shock after cross-country running. Laboratory data sh